Perceptions of Pressure and Stress Among Agile Team Members: Empirical Insights from Serbia - Lukić Nikolić, Jelena; Ostojić, Ivana; Antić, Sunčica (Industrija, 2024)
This paper investigates the perceptions of pressure and stress among agile team members, focusing on various factors, such as personal characteristics, team composition, and communication practices. Empirical research was conducted by using an online questionnaire from April to October 2024. During this time, 110 agile team members from Serbian software development companies took part in the research. Hypothesis testing, including the Mann-Whitney U-test and Kruskal-Wallis H-test, indicated no statistically significant differences by gender, age, team membership length, team size, company type, frequency of team meetings and main type of team communication. Notably, while the influence of team size approached significance, the overall results indicate that personal, teams, and organizational factors have no significant effect on perceptions of pressure and stress in agile teams. These results highlight the need for further investigation into alternative factors that may influence perceptions of pressure and stress, but they also demonstrate the superiority of agile teams.
Keywords: agile teams; workplace stress; workplace pressure; perceptions; team dynamics